A recent history of lesbian and gay psychology : from homophobia to LGBT - Hegarty, Peter (Psychology professor) (Abingdon, Oxon ; New York, NY : Routledge, 2018)
"This ground-breaking text explores the contemporary history of how psychological research, practice, and theory has engaged with gay and lesbian movements in the United States and beyond, over the last 50 years. Peter Hegarty examines the main strands of research in lesbian and gay psychology that have emerged since the de-pathologizing of homosexuality in the 1970s that followed from the recognition of homophobia and societal prejudice. The author details the expansion of 'lesbian and gay psychology' to 'LGB' to 'LGBT psychology' via its paradigm shifts, legal activism, shifts in policy makers' and mental health professionals' goals in regard to sexual and gender minorities. For the first time, the origins of the concepts, debates, and major research programs that have made up the field of LGBT psychology have been drawn together in a single historical narrative, making this a unique resource. A case is made that psychology has only very lately come to consider the needs and issues of transgender and intersex people, and that LGB paradigms need to be critically interrogated to understand how they can be best brokered to bring about social change for such groups. A Recent History of Lesbian and Gay Psychology will serve as an advanced historical introduction to this field's recent history and current concerns, and will inform both those who have been a part of this history and students who are new to the field."--Provided by publisher.
Normative creativity -- Revolutionary science -- Generalizing affirmation in the age of HIV/AIDS -- Taking the case to court -- Naturalizing and de-naturalizing sexuality in public -- Cisgenderism and LGBT affirmation.
Includes bibliographical references.
Keywords: Gays -- Psychology; Gays -- Identity; Gays -- Social conditions; Homosexuality -- Psychological aspects